Produção científica da área das Ciências Biológicas da Universidade Federal de Minas Gerais (UFMG) indexada nas bases de dados Web of Science e SCOPUS (2007 2012) - Jane Rodrigues Guirado (2015)
This study had, as main objective, analyze the characteristics of scientific production of General Biology, Botany, Morphology and Parasitology departments, belonging to the Institute of Biological Sciences, in the Federal University of Minas Gerais (ICB / UFMG),indexed in the databases Web of Science and SCOPUS. The motivation of selecting the Life Sciences area was because this field is an important research pole in UFMG and present a dynamic area. The selection of these databases was because of its multidisciplinary coverage, as well for presenting citations and indexing prestigious journals. The limitation of 06 years of research period had as the parameter the Graduate evaluation system of Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes). The themes that guided the theoretical basis of this study were: Scientific communication, formal and informal channels, Scientific Journal, Databases and Bibliometry. It is about a descriptive research with quantitative approach. Bibliometric studies were applied to achieve the goals. The universe of this research refers to the four departments of ICB / UFMG: General Biology, Botany, Morphology and Parasitology. The data collection instruments used were the databases Web of Science, Scopus, WebQualis, Journals Portal Capes, Journal Citation Reports (JCR), SCImago Journal & Country Rank (SJR) and Somos UFMG. The result of this research showed the general characteristics of the area of Biological Sciences, specifically the departments under study in the two databases. The general characteristics were identified as follows: the first scientific production presented by author showed, in the most of cases, papers with multiple authors concentrated on a small number of authors; with regard to co-authorship, collaborative network showed a higher degree of interinstitutional cooperation, at the domestic level and researchers in the same field of knowledge. However, this network also had researchers from other areas such as: Agricultural Sciences, Engineering, Health Sciences, Exact Sciences and Earth Sciences and Humanities; inreference to the preferred channel used by the authors, for the most part, has been in the form of the journal article. These periodicals presented, mostly, a high impact factor, with Qualis classification from A1 to B2, are published in European countries and are indexed in the Capes Portal of Journal collection; for the language, the most presented originaldocument are filed in the English language; with respect to collaborating institutions, most is of national and international higher education; with respect to the partner countries, it was noted cooperation with countries of the seven continents; in reference to the thematic areas of the journal titles, it was found that these titles are classified in major subject areas such as Science and Technology, Life Sciences, Exact Sciences, Social Sciences and Health Sciences; about the citation, all the most cited documents are recorded in English (except one document) and all were published in journals with high impact factor; Finally, with respect to the year, it was observed that the in the six-year period (2007/2012) occurred the growth of scientific production of these departments. With this study, it is expected that the information presented can support the Federal University of Minas Gerais in elaboration of development policies.